Calculation Ultimate Strength on Media Use Backing Ceramic Against ASTM A36 Steel by SMAW Process - Sabaruddin Rahman (Collaborate Engineering Daily Book Series, 2023)
Metal welding of large structures often requires alternating welding on both sides, which can be costly and time-consuming. However, welding results are only sometimes perfect, and gaps often require solutions to maximize welding results. One solution is using media backing ceramic as a support that can give better results. This study aims to evaluate the effect of backing ceramic and non-backing ceramics on the strength of the tensile test results on ASTM A36 steel using SMAW welding. The results of the tensile test show that there is an effect of strength on ASTM A36 steel. Mark Ultimate Tensile Strength, the highest, was obtained on specimens that did not use backing ceramics, equal to 451.893 Mpa. In contrast, the lowest value of Ultimate Tensile Strength was obtained on the specimen using backing ceramics, equal to 428.736 MPa.